ISLAMIC EDUPRENEURSHIP-BASED STRENGTHENING OF PESANTREN ECONOMY THROUGH HYDROPONIC CULTIVATION AT AL-UTSMANI ISLAMIC BOARDING SCHOOL, BONDOWOSO - Sholihah, Dawimatus; Jannah, Wildatul (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
The COVID-19 pandemic has significantly impacted the financial sustainability of Islamic boarding schools (pesantren), which predominantly rely on student fees. To address these challenges, Al-Utsmani Islamic Boarding School in Bondowoso initiated an Islamic edupreneurship-based community service program focused on hydroponic cultivation. This initiative aimed to (1) enhance the skills of students and administrators in hydroponic farming, (2) promote pesantren economic independence, and (3) integrate digital marketing and agro-tourism strategies. Implemented using the Asset-Based Community Development (ABCD) approach, the program leveraged the pesantren’s existing assets, including human resources, infrastructure, and agricultural potential. As a result, students and staff who were previously unfamiliar with hydroponic systems acquired practical farming and marketing skills. The program not only fostered entrepreneurial capacity but also laid the foundation for sustainable economic development within the pesantren environment. Nevertheless, challenges such as limited funding and market access highlight the need for further institutional and governmental support. Pandemi COVID-19 telah berdampak signifikan terhadap keberlanjutan finansial pesantren yang mayoritas bergantung pada dana dari santri. Untuk mengatasi tantangan tersebut, Pondok Pesantren Al-Utsmani Bondowoso melaksanakan program pengabdian berbasis edupreneurship Islam yang berfokus pada budidaya tanaman hidroponik. Inisiatif ini bertujuan untuk: (1) meningkatkan keterampilan santri dan pengelola pesantren dalam bercocok tanam secara hidroponik, (2) mendorong kemandirian ekonomi pesantren, dan (3) mengintegrasikan strategi pemasaran digital serta pengembangan kawasan agrowisata. Program ini dilaksanakan dengan pendekatan Asset-Based Community Development (ABCD) yang memanfaatkan berbagai aset yang telah dimiliki pesantren, termasuk sumber daya manusia, infrastruktur, dan potensi pertanian. Hasilnya, para santri dan pengelola yang sebelumnya belum mengenal sistem hidroponik kini mampu menerapkan keterampilan bercocok tanam dan strategi pemasaran produk. Program ini tidak hanya meningkatkan kapasitas kewirausahaan, tetapi juga menjadi fondasi pengembangan ekonomi berkelanjutan di lingkungan pesantren. Namun demikian, keterbatasan dana dan akses pasar menjadi tantangan yang perlu mendapat dukungan lebih lanjut dari lembaga dan pemerintah.